Linguistic Risk-Taking and Multilingual Pedagogies: Encouraging Plurilingualism in Lower Secondary Schools (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2026)
This school project, carried out regularly within a university education course at master’s level, explores the application of the Linguistic Risk-Taking (LRT) Initiative in promoting plurilingual engagement among younger secondary school students. During these week- long classroom projects, participants engage in a range of self-selected language-related challenges and reflect on their experiences during classroom discussions and in an individual written survey. Results for one such project are described here. Most school students reported developing a more positive attitude toward multilingualism and greater interest in language learning over the course of the short project, and they experimented with diverse linguistic tasks. However, they also experienced challenges with task difficulty and lack of motivation. Recommendations for further classroom projects include extending the duration of the LRT project and integrating regular structured discussions to encourage long-term student participation.
Keywords: Linguistic Risk-Taking (LRT); Practice Example; Pre-Service Teacher Training; Multilingualism Pedagogies